Clinical characteristics of XP11.2 translocation/TFE3 gene fusion renal cell carcinoma: a systematic review and meta-analysis of observational studies - Cheng, Xiangming (BMC Urol, 2016)
BACKGROUND: Renal cell carcinoma (RCC) associated with Xp11.2 translocation/TFE3 gene fusion (Xp11.2 RCC) is a rare subtype of RCC which is firstly described as a distinct entity in 2004 so that clinical characteristics of Xp11.2 RCC in different gender and age are unknown. The purpose of systematic review and meta-analysis is to provide a comprehensive assessment on them. METHODS: MEDLINE, EMBASE and Cochrane databases were searched for studies which evaluate the clinical characteristics of Xp11.2 RCC. The literature published between July 2004 and May 2014 was searched. RESULTS: A total of 15 studies with 147 participants were included. The meta-analysis demonstrated that number of patients of all age in female was higher than in male with pooled OR of 3.93(95 % CI = 1.66–9.34). However, incidence of distant metastases (OR = 0.34, 95 % CI = 0.12–1.57) and lymphatic metastases (OR = 0.51, 95 % CI = 0.14–1.91), tumor stage (OR = 0.85, 95 % CI = 0.34–2.15) and overall survival (OS) (OR = 0.46, 95 % CI = 0.05–4.34) between male and female were comparable. Incidence in female was higher than in male with pooled OR of 5.13(95 % CI = 1.67–15.72) in adults, while in children no gender-related predominance (OR = 1.19, 95 % CI = 0.38–3.72) was observed. In addition, incidence of distant metastases (OR = 1.00, 95 % CI = 0.13–7.84) and lymphatic metastases (OR = 1.00, 95 % CI = 0.07–13.67) and tumor stage (OR = 1.94, 95 % CI = 0.20–19.03) between children and adults were comparable. Survival curves presented comparable outcomes between male and female (P = 0.707) as well as between children and adults (P = 0.383). CONCLUSIONS: Female patients with Xp11.2 RCC in adults exhibit a high incidence compared to male, but not in children. Comparable clinical characteristics including incidence of distant and lymphatic metastases, tumor stage and prognosis is presented between male and female as well as between children and adults.